Deconstructing Material Commodification: A Feminist Critique of Objectification in Qaisra Shahraz’s Holy Woman - Saeed, Omera; Ilyas, Aneela; Zulfiqar, Shiza; Ajmal , Muhammad (Pakistan Journal of Humanities and Social Sciences, 2024)
The main concernof present study is to analyze Qaisra Shahraz’s Holy Woman by applying feministic lens and Simon de beaviour Second Sex Theoretical lens to discuss the materialistic commodification that influence the women individuality and identity as a woman. Using the objectification concept and feminist criticism, the study examines how the leading character Zarri Bano as targeted and objectified by her own .An examination of the material and /or trading concept of woman is then used through a detailed textual analysis to break down how various factors of sexualization, money, and femininity develop the women’s realities, their identity, and the systems of opposition available to them. This research delves into the patriarchal power dynamics that objectify and silence women's voices, particularly focusing on the subjugation of female subalterns by patriarchal forces. It highlights how these power structures manipulate discourse to impose specific identities on women, such as Holy women, izzat, gairat, purdah, and burqa to serve patriarchal agendas rather than genuine religious principles. Through the lens of Simon de Beauvoir's feminist philosophy, this study examines the character of Zari Bano in Qaisra Shahraz's novel Holy Woman as a symbol of subalternity, revealing the oppression she faces not only from her father but also from societal discrimination based on gender. The analysis demonstrates how patriarchal societies justify the marginalization of women to advance their own political and economic interests.